RSU-Aided Remote V2V Message Dissemination Employing Secure Group Association for UAV-Assisted VANETs - Haowen Tan (Electronics, 2021)
Nowadays, the research on vehicular ad hoc networks (VANETs) remains a hot topic within the Internet of Things (IoT) scenarios. Diverse studies and techniques regarding all aspects of VANETs have been investigated thoroughly. Particularly, the wireless characteristic of heterogeneous vehicular communication, along with the complicated and dynamic connection topology among participating VANET entities, have severely affected the secure and stable data exchange. Specifically, the spontaneous vehicle-to-vehicle (V2V) message dissemination, as the essential functionality of VANET, plays a significant role for instant and real-time data sharing for vehicles within a certain vicinity. However, with the short-time interaction and high mobilization of vehicular connections, the remote V2V message delivery intended for long-distance vehicles in the range of different roadside units (RSUs) has not been properly researched. Meanwhile, both V2V and V2R (Vehicle-to-RSU) communication are highly restricted by environmental factors such as physical obstructions or signal interferences, thus drastically reducing the wireless connectivity in practical VANET implementations. In this case, the unmanned aerial vehicles (UAVs), as the auxiliary facilities, can provide the VANET with substitute wireless routes, so that the transmission quality and availability can be improved. In this paper, the authenticated UAV group association design is proposed at first. On this basis, the remote V2V message dissemination method is enabled, where the decentralized V2V connections involving all RSUs along the way are provided. The analysis regarding crucial security properties is presented accordingly, where the formal proofs and comparison are conducted. Moreover, the performance evaluation in terms of storage and time consumption during RSU authentication process is illustrated, respectively. Comparison results with the state-of-the-art prove that superiority on the major performance factors can be achieved.